High-purity strontium metasilicate powder and preparation method thereof

By coating nanosilicon dioxide on the surface of the strontium source, the high-temperature solid-phase sintering was solved, and problems such as high reaction temperature and impure composition segregation in the existing strontium metasilicate preparation method were successfully prepared, which achieved process simplification and environmental protection.

CN119750601APending Publication Date: 2025-04-04SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411833195.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing preparation methods of strontium metasilicate have problems such as many chemical residues, high impurity content, large environmental pollution, high reaction temperature, and impure components segregation.

Method used

High-purity strontium metasilicate powder was prepared by sintering the silicon source on the surface of the strontium source by high-temperature solid phase. The specific steps include ultrasonic dispersing of the nano-silicon dioxide powder in anhydrous ethanol to form a dispersion liquid, then ball milling, drying, grinding, sieve with a strontium source, and finally sintering to obtain a high-purity strontium metasilicate powder.

Benefits of technology

The preparation of high purity (≥99%) strontium metasilicate powder was achieved, which solved the problems of high reaction temperature and impure components in traditional methods, and simplified process steps, reducing impurity content and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750601A_ABST
    Figure CN119750601A_ABST
Patent Text Reader

Abstract

The invention relates to high-purity strontium metasilicate powder and a preparation method thereof. The preparation method of the high-purity strontium metasilicate powder comprises the following steps: adding a silicon source into absolute ethyl alcohol for ultrasonic dispersion to form dispersion liquid; adding a proper amount of a strontium source into the dispersion liquid, and carrying out ball milling, drying, grinding and sieving to obtain mixed powder with the surface of the strontium source coated with a silicon source; and sintering the mixed powder to obtain the high-purity strontium metasilicate powder. The preparation method provided by the invention has the advantages of simple steps, simple equipment and easily available raw materials, and can be used for batch production of the strontium metasilicate powder with high purity and few impurities, and the purity of the obtained high-purity strontium metasilicate powder is greater than or equal to 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and relates to a strontium metasilicate powder and a preparation method thereof, and specifically relates to a high-purity strontium metasilicate powder and a preparation method thereof. Background Art

[0002] Strontium metasilicate (SrSiO3) is a widely used inorganic material. As a solid lubricant, it can improve the high-temperature friction performance of materials. As a sintering accelerator, it can accelerate the sintering of composite materials. When doped in materials containing rare earth elements, it can improve their luminescence performance. In addition, metasilicate and strontium are both trace elements that are beneficial to the human body. They are commonly found in high-quality mineral water and can prevent cardiovascular diseases.

[0003] At present, the preparation methods of strontium metasilicate are mainly sol-gel method, chemical precipitation method and high-temperature solid phase method. Sol-gel method and chemical precipitation method are affected by the preparation process, and there are many chemical residual products, high impurity content and great environmental pollution in the preparation process. Strontium metasilicate prepared by high-temperature solid phase method usually has problems such as high reaction temperature, impure component segregation, etc. Summary of the invention

[0004] In view of the above problems, the present invention prepares a high-purity strontium metasilicate powder by coating a silicon source (nano silicon dioxide powder) on the surface of a strontium source (strontium carbonate, strontium hydroxide) and then sintering the resultant product by a high-temperature solid phase method.

[0005] On the one hand, the present invention provides a method for preparing high-purity strontium metasilicate powder, comprising: adding a silicon source to anhydrous ethanol and ultrasonically dispersing it to form a dispersion; adding an appropriate amount of strontium source to the dispersion, ball milling, drying, grinding, and sieving to obtain a mixed powder in which the surface of the strontium source is coated with the silicon source; and sintering the mixed powder to obtain the high-purity strontium metasilicate powder.

[0006] Preferably, the silicon source is nano-silicon dioxide; the particle size of the nano-silicon dioxide is 10 to 50 nm.

[0007] Preferably, the ultrasonic dispersion time is 1 to 2 hours.

[0008] Preferably, the concentration of the dispersion is 7.5-10%.

[0009] Preferably, the strontium source is strontium carbonate and / or strontium hydroxide; the particle size of the strontium source is 0.5-1.0 μm.

[0010] Preferably, the molar ratio of the strontium source to the silicon source is 1:1.

[0011] Preferably, the particle size ratio of the strontium source to the silicon source is 1:100 to 1:10.

[0012] Preferably, the ball milling is wet ball milling; the parameters of the wet ball milling include: a ball milling speed of 80 to 120 r / min, a ball milling time of 3 to 5 h, and anhydrous ethanol as the solvent.

[0013] Preferably, the drying temperature is 80-120° C. and the drying time is 12-24 hours.

[0014] Preferably, the mesh size of the sieving is 20 to 60 meshes.

[0015] Preferably, the sintering temperature is 1380-1420° C. and the sintering time is 2-4 hours.

[0016] On the other hand, the present invention also provides a high-purity strontium metasilicate powder prepared by the above preparation method, wherein the purity of the high-purity strontium metasilicate powder is ≥99%.

[0017] Beneficial effects: (1) In high-temperature solid-phase reactions, surface contact between reactants is a prerequisite for chemical reactions and material diffusion. In order to allow the strontium source and the silicon source to react fully, the present invention first disperses the nanometer-sized silicon source uniformly in anhydrous ethanol to form a dispersion, then coats it on the surface of the submicron-sized strontium source, and then uses mechanical ball milling to allow them to fully contact, thereby solving the problems of high reaction temperature, component segregation and impurity in traditional high-temperature solid-phase reactions. (2) The preparation method provided by the present invention has simple steps, simple equipment, readily available raw materials, and can mass-produce strontium metasilicate powder with high purity and few impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The X-ray diffraction pattern of the high-purity strontium metasilicate powder prepared in Example 1-3; Figure 2 This is the X-ray diffraction pattern of the strontium metasilicate powder prepared in Comparative Examples 1-3. DETAILED DESCRIPTION

[0019] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0020] In the present invention, a nanometer-sized silicon source (nano silicon dioxide) is first uniformly dispersed in anhydrous ethanol to form a dispersion, and then a strontium source is added thereto, and the silicon source is coated on the surface of the submicron-sized strontium source by mechanical ball milling, and then sintered by a high-temperature solid phase method to prepare a high-purity strontium metasilicate powder. Among them, in order to increase the surface contact between the reactants, accelerate the chemical reaction and material diffusion, that is, accelerate the full reaction of the strontium source and the silicon source, the present invention fully disperses the nanometer-sized silicon source and then coats it on the surface of the submicron-sized strontium source, which greatly promotes the reaction diffusion between the substances in the chemical reaction, improves the powder purity and shortens the reaction time. In the present invention, the key to improving the powder purity is that the silicon source is fully dispersed and uniformly coated on the surface of the strontium source. If the nano silicon dioxide is not completely dispersed, its agglomerates cannot be effectively opened and cannot be uniformly coated on the surface of the strontium source. At high temperature, the nano-sized silicon source and the strontium source undergo the following reaction: 2SrO+SiO2→Sr2SiO4, and further Sr2SiO4+SiO2→2SrSiO3. If the nano-silicon dioxide cannot be evenly dispersed, local silica agglomeration and enrichment will lead to low silica content in other areas, then 2SrO+SiO2→Sr2SiO4 will occur, and the reaction Sr2SiO4+SiO2→2SrSiO3 will not occur, thereby affecting the uniform formation of SrSiO3 and producing Sr2SiO4 impurity phase.

[0021] In the present invention, by adjusting the appropriate dispersion concentration, ultrasonic dispersion time and the particle size ratio of the strontium source to the silicon source, the various parameters are coordinated with each other to achieve uniform coating of the silicon source. Specifically, if the dispersion concentration is too low, the surface of the strontium source partially contacts the nano-silicon dioxide, resulting in incomplete coating; if the dispersion concentration is too high, the viscosity of the dispersion system will increase, affecting the fluidity and dispersibility of the particles during the coating process, and thus affecting the coating effect. If the ultrasonic dispersion time is too short, the nano-silicon dioxide will not be dispersed completely, and the agglomerates cannot be effectively opened; if the ultrasonic dispersion time is too long, the surface charge distribution of the nano-silicon dioxide will change or the adsorption layer on the surface of the particles will be destroyed, causing the particles to re-agglomerate. If the particle size ratio of the strontium source to the silicon source is too large, due to the large specific gravity of the strontium source, sedimentation will occur during the drying process, resulting in component segregation; if the particle size ratio of the strontium source to the silicon source is too small, it is difficult to form an effective coating, reducing the reaction interface, and affecting the subsequent solid-phase reaction to be fully carried out.

[0022] In the present invention, the purpose of uniformly dispersing the nanometer-sized silicon source in anhydrous ethanol to form a dispersion is to achieve the depolymerization of the silicon source. Ordinary silicon dioxide is a polar oxide and has good dispersibility in anhydrous ethanol medium, while the nano silicon dioxide used in the present invention has a large specific surface area, strong interaction between particles, easy to agglomerate, and greater difficulty in dispersion. Therefore, the present invention first dissolves the nano silicon dioxide in anhydrous ethanol, and then controls the ultrasonic dispersion time to be 1 to 2 hours, the main purpose is to fully depolymerize and disperse the nano silicon dioxide, and keep it stable. Without this step, the nano silicon dioxide will be incompletely dispersed, the agglomerates cannot be effectively opened, and local silicon dioxide will be enriched, which will lead to low silicon dioxide content in other areas, affecting the reaction of Sr2SiO4+SiO2→2SrSiO3, and finally affecting the purity of the product SrSiO3.

[0023] The following is an exemplary description of the method for preparing the high-purity strontium metasilicate powder provided by the present invention.

[0024] The silicon source is added into anhydrous ethanol and ultrasonically dispersed to form a dispersion.

[0025] In an optional embodiment, the silicon source is nano-silicon dioxide; the particle size of the nano-silicon dioxide is 10 to 50 nm.

[0026] In an optional embodiment, the concentration of the dispersion is 7.5-10%. If the concentration of the dispersion is too low, the surface of the strontium source partially contacts the nano-silicon dioxide, resulting in incomplete coating; if the concentration of the dispersion is too high, the viscosity of the dispersion system increases, affecting the fluidity and dispersibility of the particles during the coating process, thereby affecting the coating effect.

[0027] In an optional embodiment, the ultrasonic dispersion time is 1 to 2 hours. If the ultrasonic dispersion time is too short, the nano-silicon dioxide will not be fully dispersed and the agglomerates cannot be effectively opened; if the ultrasonic dispersion time is too long, the surface charge distribution of the nano-silicon dioxide will change or the adsorption layer on the surface of the particles will be destroyed, causing the particles to re-agglomerate.

[0028] A strontium source is added to the dispersion, and mixed powder is obtained through ball milling, drying, grinding and sieving.

[0029] In an optional embodiment, the strontium source is strontium carbonate and / or strontium hydroxide; the particle size of the strontium source is 0.5 to 1.0 μm. The molar ratio of the strontium source to the silicon source is 1:1. The particle size ratio of the strontium source to the silicon source is 1:100 to 1:10. If the particle size ratio of the strontium source to the silicon source is too large, sedimentation will occur during the drying process due to the large specific gravity of the strontium source, resulting in component segregation; if the particle size ratio of the strontium source to the silicon source is too small, it is difficult to form an effective coating, reduce the reaction interface, and affect the subsequent solid phase reaction.

[0030] In an optional embodiment, the ball milling is wet ball milling; the parameters of the wet ball milling include: the ball milling speed is 80-120 r / min, the ball milling time is 3-5 hours, the solvent is anhydrous ethanol, the drying temperature is 80-120° C., the time is 12-24 hours, and the mesh size of the sieve is 20-60 meshes.

[0031] The mixed powder is sintered and then cooled to room temperature to obtain a white strontium metasilicate block.

[0032] In an optional embodiment, the sintering temperature is 1380-1420° C., and the sintering time is 2-4 hours.

[0033] The obtained strontium metasilicate block is ground and sieved to obtain the high-purity strontium metasilicate powder.

[0034] In an optional embodiment, the mesh size of the sieving is 60 to 120 meshes.

[0035] In the present invention, the purity of the high-purity strontium metasilicate powder is ≥99%.

[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0037] Example 1 First, 1 mol of nano-silicon dioxide powder with a particle size of 10-20 nm is added to 690 g of anhydrous ethanol and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 8%. Then, 1 mol of strontium carbonate powder with a particle size of 0.5-1.0 μm is added to the dispersion, and after wet ball milling for 4 hours, it is dried at 80°C, ground and sieved through a 20-mesh sieve to obtain a mixed powder; the mixed powder is placed in a muffle furnace and sintered at 1420°C for 3 hours, and then cooled to room temperature to obtain a SrSiO3 block; the obtained SrSrO3 block is ground and sieved through a 60-mesh sieve to obtain a white strontium metasilicate powder.

[0038] The obtained powder was tested by X-ray diffraction (such as Figure 1 As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this embodiment 1 has no impurity phase. The purity of the strontium metasilicate powder obtained in this embodiment 1 is ≥99%.

[0039] Example 2 First, 1 mol of nano-silicon dioxide powder with a particle size of 10-40 nm is placed in 720 g of anhydrous ethanol and ultrasonically dispersed for 3 hours to form a dispersion with a concentration of 7.5%. Then, 1 mol of strontium carbonate powder with a particle size of 0.5-1.0 μm is placed in the dispersion, wet ball milled for 4 hours, dried at 80°C, and then ground and sieved through a 20-mesh sieve to obtain a mixed powder; the mixed powder is placed in a muffle furnace and sintered at 1380°C for 4 hours, then cooled to room temperature to obtain a SrSiO3 block; the obtained SrSrO3 block is ground through a 60-mesh sieve to obtain a white strontium metasilicate powder.

[0040] The obtained powder was tested by X-ray diffraction (such as Figure 1 As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this embodiment 2 has no impurity phase. The purity of the strontium metasilicate powder obtained in this embodiment 2 is ≥99%.

[0041] Example 3 First, 1 mol of nano-silicon dioxide powder with a particle size of 10 to 50 nm is placed in 540 g of anhydrous ethanol and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 10%. Then, 1 mol of strontium hydroxide powder with a particle size of 0.5 to 1.0 μm is placed in the dispersion, wet ball milled for 5 hours, dried at 80°C, and then ground and sieved through a 60-mesh sieve to obtain a mixed powder; the mixed powder is placed in a muffle furnace, sintered at 1400°C for 4 hours, and then cooled to room temperature to obtain a SrSiO3 block; the obtained SrSrO3 block is ground and sieved through a 120-mesh sieve to obtain a white strontium metasilicate powder.

[0042] The obtained powder was tested by X-ray diffraction (such as Figure 1 As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this embodiment 3 has no impurity phase. The purity of the strontium metasilicate powder obtained in this embodiment 3 is ≥99%.

[0043] Comparative Example 1 First, 1 mol of nano-silicon dioxide powder with a particle size of 10-20 nm is added to 940 g of anhydrous ethanol and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 6%. Then, 1 mol of strontium carbonate powder with a particle size of 0.5-1.0 μm is added to the dispersion, and after wet ball milling for 4 hours, it is dried at 80°C, ground and sieved through a 20-mesh sieve to obtain a mixed powder; the mixed powder is placed in a muffle furnace and sintered at 1420°C for 3 hours, and then cooled to room temperature to obtain a SrSiO3 block; the obtained SrSrO3 block is ground and sieved through a 60-mesh sieve to obtain a white strontium metasilicate powder.

[0044] The obtained powder was tested by X-ray diffraction (such as Figure 2As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this comparative example 1 contains Sr2SiO4 impurity phase. Due to the low concentration of the dispersion liquid, the purity of the strontium metasilicate powder obtained in the comparative example 1 of the present invention is 84.1%.

[0045] Comparative Example 2 First, 1 mol of nano-silicon dioxide powder with a particle size of 10-20 nm is added to 690 g of anhydrous ethanol and ultrasonically dispersed for 0.5 h to form a dispersion with a concentration of 8%. Then, 1 mol of strontium carbonate powder with a particle size of 0.5-1.0 μm is added to the dispersion, and after wet ball milling for 4 h, it is dried at 80°C, ground and sieved through a 20-mesh sieve to obtain a mixed powder; the mixed powder is placed in a muffle furnace and sintered at 1420°C for 3 h, and then cooled to room temperature to obtain a SrSiO3 block; the obtained SrSrO3 block is ground and sieved through a 60-mesh sieve to obtain a white strontium metasilicate powder.

[0046] The obtained powder was tested by X-ray diffraction (such as Figure 2 As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this comparative example 2 contains Sr2SiO4 impurity phase. Due to the short ultrasonic time, the purity of the strontium metasilicate powder obtained in the comparative example 2 of the present invention is 88.5%.

[0047] Comparative Example 3 First, 1 mol of nano-silicon dioxide powder with a particle size of 60-100 nm is added to 690 g of anhydrous ethanol and ultrasonically dispersed for 2 hours to form a dispersion with a concentration of 8%. Then, 1 mol of strontium carbonate powder with a particle size of 0.5-1.0 μm is added to the dispersion. After wet ball milling for 4 hours, the mixture is dried at 80°C, ground and sieved through a 20-mesh sieve to obtain a mixed powder. The mixed powder is placed in a muffle furnace and sintered at 1420°C for 3 hours, then cooled to room temperature to obtain a SrSiO3 block. The obtained SrSrO3 block is ground and sieved through a 60-mesh sieve to obtain a white strontium metasilicate powder.

[0048] The obtained powder was tested by X-ray diffraction (such as Figure 2 As shown in the figure, it can be seen that the strontium metasilicate powder prepared in this comparative example 3 contains Sr2SiO4 impurity phase. Since the particle size ratio of the strontium source to the silicon source is too small, the purity of the strontium metasilicate powder obtained in comparative example 3 of the present invention is 84.3%.

Claims

1. A method for preparing high-purity strontium metasilicate powder, characterized in that: include: The silicon source is added to anhydrous ethanol and ultrasonically dispersed to form a dispersion; an appropriate amount of strontium source is added to the dispersion, and the mixture is ball-milled, dried, ground, and sieved to obtain a mixed powder in which the surface of the strontium source is coated with the silicon source; the mixed powder is sintered to obtain the high-purity strontium metasilicate powder.

2. The preparation method according to claim 1, characterized in that: The silicon source is nano-silicon dioxide; the particle size of the nano-silicon dioxide is 10 to 50 nm; The strontium source is strontium carbonate and / or strontium hydroxide; the particle size of the strontium source is 0.5-1.0 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The particle size ratio of the strontium source to the silicon source is 1:100 to 1:

10.

4. The preparation method according to any one of claims 1 to 3, characterized in that The ultrasonic dispersion time is 1 to 2 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The concentration of the dispersion is 7.5-10%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The molar ratio of the strontium source to the silicon source is 1:

1.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The ball milling is wet ball milling; the parameters of the wet ball milling include: the ball milling speed is 80-120r / min, the ball milling time is 3-5h, and the solvent is anhydrous ethanol; The drying temperature is 80-120° C. and the drying time is 12-24 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering temperature is 1380-1420° C. and the sintering time is 2-4 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The mesh number of the sieving is 20 to 60 meshes.

10. A high-purity strontium metasilicate powder prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The purity of the high-purity strontium metasilicate powder is ≥99%.